Perivascular adipose tissue and vascular inflammation: from biological insights to clinical implications - Sowa, Hiroyuki; Karasaki, Kohei; Ishiwata, Mai; Cheng, Xu; Hashimoto, Masaki; Ueda, Kazutaka (Frontiers in Physiology, 2026)
Perivascular adipose tissue (PVAT) has emerged as an active paracrine and metabolic organ that modulates vascular function in both humans and rodents, rather than serving merely as structural support. Vascular inflammation is a central mechanism driving cardiovascular diseases such as atherosclerosis, representing a maladaptive response to vascular injury. Recent evidence indicates that PVAT actively participates in this process through dynamic phenotypic changes, including adipose tissue browning or beiging. Furthermore, advances in imaging have enabled the noninvasive evaluation of vascular inflammation using computed tomography–derived indices that reflect PVAT characteristics. This review summarizes current understanding of the interplay between PVAT and vascular inflammation, highlights the biological and clinical implications of PVAT remodeling, and discusses emerging diagnostic approaches and future research directions.